Human papillomavirus-associated cancers: a survey on otorhinolaryngologists' knowledge and attitudes on prevention - ODONE, A. (Acta Otorhinolaryngol Ital, 2015)
Human papillomavirus (HPV) infection is a recognised causal factor associated with oropharyngeal cancers. The global burden of HPVrelated oropharyngeal cancers is on the increase and is predicted to surpass the burden of cervical cancer in the near future. As evidence is accumulating on the potential effectiveness of an HPV vaccine in controlling the oropharyngeal cancer epidemic; otorhinolaryngologists assume a key role – not only in the diagnosis and treatment of HPV-related cancers – but also in educating and advocating on HPV prevention. We conducted a survey to assess Italian otorhinolaryngologists' knowledge and attitudes regarding HPV infection, HPV-related oropharyngeal diseases and cancers and available prevention measures, including vaccines. This is the first study conducted in Italy and Europe on this topic. A total of 262 Italian otorhinolaryngologists were recruited during the National Conference of the Italian Association of Otorhinolaryngologists. Our results show that Italian otorhinolaryngologists are knowledgeable regarding HPV infection and have a positive attitude towards HPV vaccine. Our findings provide a useful basis to plan, implement and evaluate targeted educational programmes and training. As we show herein, educational programmes and training specifically focusing on HPV are effective in increasing physicians' knowledge and positive attitudes towards prevention; this ultimately contributes to enhance vaccine uptake among patients and the general population. With the overall aim of controlling the burden of HPV-related cancers, resources and efforts should be devoted to promote continuing education among otorhinolaryngologists and the general medical community and to increase awareness on the role of vaccines in prevention of HPV-related cancers. In this context, there is tremendous opportunity for healthcare providers across fields to cooperate and for public health and otorhinolaryngologist communities to join forces and engage in fruitful collaboration.